PERKAHWINAN KANAK-KANAK DAN TAHAP MINIMA UMUR PERKAHWINAN DALAM UNDANG-UNDANG KELUARGA ISLAM: Child Marriage And Minimum Age of Marriage Under Islamic Family Law - Noor, Zanariah (Jurnal Syariah, 2019)
Child marriage is not a new topic of debate within the Muslim society. Different understandings and tendencies in interpreting the laws on such an issue among Muslims has sometimes led to conflicts in the society. The discussion regarding child marriage is closely related to the issues of puberty according to Islamic law as well as the readiness of the child to engage in sexual intercourse and the approaches taken by Islamic countries, including Malaysia, to tackle such issues. This article discusses the above mentioned aspects according to Islamic law in classical Fiqh books and also provides comparisons between Islamic family law statutes in other countries.